IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH PROBLEM-BASED LEARNING MODEL IN 5TH GRADE OF SDN 235 PALEMBANG - Marini, Sulastri; Nopri, Nopri; Waty, Evy Ratna Kartika (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2023)
This research was conducted due to the identified issue within the classroom: the low learning outcomes of students in mathematics and their lack of familiarity with critical thinking, resulting in passivity. This research aimed to improve mathematics learning outcomes through the Problem-Based Learning (PBL) model for 5th grade students in SD Negeri 235 Palembang. This research used the classroom action research (CAR) method, conducted over two learning cycles. The research subjects were 23 students in 5th grade. This research used a learning outcome test instrument as the data collection technique. This research demonstrated that the problem-based learning model could improve students’ learning outcomes. In the pre-cycle stage, 43% of students achieved competence with an average score of 64.7. There was an improvement in cycle I, with 65.2% of students achieving competence with an average score of 70.4. Furthermore, in cycle II, the score improved to 87%, with an average score of 87.6.